Mechanisms underlying the hypotensive and vasodilator effects of Ru(terpy)(bdq)NO](3+), a nitric oxide donor, differ between normotensive and spontaneously hypertensive rats - Potje, Simone R. [UNESP]; Munhoz, Felipe C. [UNESP]; Perassa, Ligia A. [UNESP]; Graton, Murilo E. [UNESP]; Pereira, Ariana A. F. [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Silva, Roberto S. da; Bendhack, Lusiane M.; Sumida, Doris Hissako [UNESP]; Silva, Cristina Antoniali [UNESP] (Elsevier B.V., 2014)
The endothelium impairs the vasodilator effect of Ru(terpy)(bdq)NO](3+) (TERPY) in Wistar rat aortas. We hypothesized that endothelial dysfunction could modulate TERPY's effect in spontaneously hypertensive rats. The present study investigated the role of the endothelium in the hypotensive and vasodilator effects of TERPY in spontaneously hypertensive rats. We observed a higher hypotensive effect of TERPY in spontaneously hypertensive than in Wistar rats. L-N-G-Nitroarginine methyl ester, a nitric oxide synthase inhibitor, increased TERPY's hypotensive effect in Wistar but not in spontaneously hypertensive rats. TERPY induced a concentration-dependent vasodilator effect in aortas of both rat models. Endothelium removal or L-NAME increased TERPY's potency in Wistar rat aortas; this effect was decreased in spontaneously hypertensive rats. TERPY increased nitric oxide level in spontaneously hypertensive rat endothelial cells; this increase was abolished in the presence of L-NAME. In contrast, this effect was increased in Wistar rats. TERPY, with or without c-NAME, decreased levels of reactive oxygen species in spontaneously hypertensive rat endothelial cells. However, it increased these levels in Wistar rats. TERPY reduced aortic endothelial nitric oxide synthase expression in Wistar rats, but did not alter its expression in spontaneously hypertensive rats. In conclusion, different mechanisms underlie the hypotensive and vasodilator effects of TERPY in these two rat models. TERPY reduced endothelial nitric oxide synthase expression and increased reactive oxygen species production in Wistar rat aortas, but did not alter these in spontaneously hypertensive rats. Furthermore, the nitric oxide released by TERPY reacts with reactive oxygen species, decreasing their bioavailability in spontaneously hypertensive rats. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Spontaneously hypertensive rats; Endothelium; Nitric oxide donor; Hypotensive effect; Vasodilator effect